2017
DOI: 10.1111/jse.12261
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence morphology and development in the basal rosid lineage Vitales

Abstract: This review summarizes inflorescence developmental morphology in the grape order Vitales within a phylogenetic context. Inflorescences in the shrubby Leeaceae are terminal thyrses that appear leaf-opposed once renewal growth begins. Plants of the Vitaceae are mainly tendrilled lianas and form five well-defined clades. Inflorescences develop from the unique, non-leafy, uncommitted primordium which arises opposite a leaf on the flank of the shoot apical meristem, and may mature into an inflorescence, tendril, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…At present, with the advent of modern phylogenetics and a better understanding of the relationships among lineages (e.g., Wen et al, , ; Ren et al, ; Liu et al, ; Habib et al, ; Lu et al, ), it is now important to revisit the morpho‐anatomical diversity within this economically and ecologically important family in search for morphological, developmental and anatomical characters that potentially support lineages/clades delimited by DNA sequence data. From this new perspective, it will be possible to establish morpho‐anatomical synapomorphies within the various lineages in the family (Gerrath et al, ; Wen et al, ). Here we provide the first step towards this anatomical reappraisal, starting by discussing the presence of a cambial variant known as successive cambia in Tetrastigma , and describing in detail its ontogeny in Tetrastigma voinierianum (Baltet) Gagnep.…”
Section: Introductionmentioning
confidence: 99%
“…At present, with the advent of modern phylogenetics and a better understanding of the relationships among lineages (e.g., Wen et al, , ; Ren et al, ; Liu et al, ; Habib et al, ; Lu et al, ), it is now important to revisit the morpho‐anatomical diversity within this economically and ecologically important family in search for morphological, developmental and anatomical characters that potentially support lineages/clades delimited by DNA sequence data. From this new perspective, it will be possible to establish morpho‐anatomical synapomorphies within the various lineages in the family (Gerrath et al, ; Wen et al, ). Here we provide the first step towards this anatomical reappraisal, starting by discussing the presence of a cambial variant known as successive cambia in Tetrastigma , and describing in detail its ontogeny in Tetrastigma voinierianum (Baltet) Gagnep.…”
Section: Introductionmentioning
confidence: 99%
“…The inflorescences of Tetrastigma have been characterized as axillary, pseudo‐terminal, or leaf‐opposed (Chen et al, ). However, Gerrath et al () suggested that the inflorescence in the CCT clade ( Cayratia s.s., Causonis, Cyphostemma , and Tetrastigma ) is leaf‐opposed on a compressed axillary shoot, based on evidence from inflorescence development in T. pubinerve Merr. & Chun and T. voinierianum Pierre ex Gagnep.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its importance to angiosperm diversification, our knowledge of the evolutionary patterns and the underlying developmental and genetic basis of the floral display is still limited. In the modern times, with the advent of integrating approaches among phylogenetics, ecology, molecular genetics, and development, plant biologists have begun to shed lights on the evolutionary patterns, the underlying driving forces, and the developmental and molecular basis of the floral diversity in some angiosperm lineages (e.g., Gerrath et al, ; Kulbaba et al, ; Liu et al, ; Nikolov & Davis, ; Schrager‐Lavelle et al, ; Zhang et al, ; see review by Ma et al, , this issue).…”
mentioning
confidence: 99%
“…Most works presented at the symposium were included in this special issue of Journal of Systematics and Evolution . This issue includes both reviews and research papers reporting works on diverse angiosperm lineages, from dicots (Gerrath et al, ; Kulbaba et al, ; Liu et al, ; Nikolov & Davis, ; Zhang et al, ) to monocots (Schrager‐Lavelle et al, ), from autotrophs (Gerrath et al, ; Kulbaba et al, ; Liu et al, ; Schrager‐Lavelle et al, ; Zhang et al, ) to heterotrophs (Nikolov & Davis, ), and from ecological (Kulbaba et al, ) to morphological and molecular aspects (Gerrath et al, ; Liu et al, ; Nikolov & Davis, ; Schrager‐Lavelle et al, ; Zhang et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation